Analysis of cervical abrasions requiring rct - a retrospective study - T, PRIADARSINI; K, SOWMYA; GANAPATHY, DHANRAJ (The journal of contemporary issues in business and government, 2020)
Cervical abrasion is the wear of the hard tissues in the neck of the tooth, produced by a constant frictional mechanical process. Clinically, cervical abrasion initially appears as a small horizontal groove near the cementoenamel junction. Later , on progression , the walls form a wedge with polished glassy surfaces. These lesions usually have a multi-causal origin. Dental abrasion is most commonly seen at the cervical necks of the teeth, but can also occur in the interdental area from vigorous and incorrect use of dental floss. Toothbrush abrasion has long been held as the prime cause of cervical abrasions. Mild cervical abrasions can be restored , whereas deep cervical lesions have to be treated endodontically or extracted based on the prognosis of the tooth. The aim of the study was to determine the number and teeth distribution of cervical abrasions requiring root canal treatment and to evaluate its association with age and gender. Totally 115 patients who had cervical abrasions with pulpal involvement visiting Saveetha dental College for treatment were included in the study. A total of 173 teeth with cervical abrasions requiring endodontic treatment were identified. Data tabulated in excel sheet and exported to IBM SPSS software version 20.0. The results showed that more than half the teeth affected were the premolars (56.07%). Males and population in the age group 40-60 years had more number of teeth with cervical abrasions requiring root canal treatment. A significant association was found for the type of teeth affected with age (P value- 0.030 >0.05; Fisher’s exact test) but not with gender(P value- 0.219 >0.05; Chi square test). Early diagnosis and intervention can prevent the progress of the cervical lesion.